Modeling and application of piezoelectric transducers for structural health monitoring - Sabet Divsholi Bahador (2012)
The last few decades have witnessed vast applications of smart materials in structural health monitoring (SHM). Piezoelectric lead zirconate titanate (PZT) transducers are robust, cost effective, sensitive to damage, and ideal for monitoring constructed infrastructures. However PZT is brittle and cannot be installed on the curve surfaces. On the other hand, the newly developed macro fiber composites (MFC) are flexible, durable and damage tolerant. The MFC is good sensor and very strong actuator. However it is less sensitive as sensor for the same level of applied electrical charge compared to PZT. In this work, one and two dimensional strain transfer models with inclusion of adhesive layer are developed. A finite element model (FEM) using ABAQUS for actuation of a cantilever beam with MFC actuator is performed. An experimental test is carried out and the results are compared with the FEM and analytical results. The developed model is useful for the applications such as vibration control, sensing and actuation where the stiffnesses of the host structure and actuator are comparable. By incorporating the developed strain transfer model, the existing electromechanical impedance (EMI) model for SHM is improved. A reduction factor is derived analytically and parametric study is performed on the reduction factor. A finite element model is developed in ANSYS to numerically investigate and verify the effect of epoxy layer properties on the sensitivity of PZT transducer. The root mean square deviation (RMSD) method has been used extensively in the EMI technique for SHM. However, study on identification of damage severity and location is still in need. This work proposes a new approach for damage identification by calculating the RMSD values of sub-frequency intervals (RMSD-S) in a large frequency range. The proposed RMSD-S based damage identification method reduces inconsistency and uncertainties in the traditional RMSD method which uses limited high frequency range. Using the observation that the damage close to the PZT changes the RMSD-S at high frequency range significantly and the damage far away from the PZT changes the RMSD-S at low frequency range significantly, the location and severity of damage can be assessed. To reduce the cost of PZT based SHM, a reusable PZT setup for monitoring initial hydration of concrete and structural health is developed. The results show that the developed transducer is able to effectively monitor the initial hydration of concrete and can be detached from the concrete for future use.